Hubungan Faktor Lingkungan Kerja dan Praktek Pengelolaan Pestisida dengan Kejadian Keracunan Pestisida Pada Tenaga Kerja di Tempat Penjualan Pestisida di Kabupaten Subang - Pujiono, Pujiono; Suhartono, Suhartono; Sulistiyani, Sulistiyani (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2009)
ABSTRACT Background: The production of agriculture in developing countries increase because of pesticides using to control pest in agriculture. Pesticides are poison and dangerous materials. It can cause negative effects. District of Subang is one of many district in West Java producted of agriculture. This research was conducted in District of Subang when found 330 seller/retailer of pesticide and they are not cholinesterase activity examination. The aim of this research was to study was factors that related to pesticide poisoning on worker who work in pesticide retailers. Method: The research done observationally through cross sectional approach, the population was all worker of pesticide retailers at Sub District of Pamanukan, Pusakanagara, Pusakajaya and Tambak Dahan. The sample of this research were 62 people taken with simple random sampling. Data would be analyzed using Chi-square and logistic regression techniques. Result: The research showed significant relationship between working environment sanitation (p=0,018), protective equipment (p=0,012) and practice of pesticide management (p=0,002). The analytic data using logistic regretion test was found 2 variable had influence directly, namely personal protectif equipment (p=0,049) and practice of pesticide management (p=0,021). Conclusion:The cholinesterase examination on worker of pesticide retailers who protective got pesticide poisoning was measwed 66,1%. To avoid pesticide poisoning, it is suggested to give training to the owner and workers, use personal protective equipment, inspection related to the health of the worker periodically, and improve the environment sanitation of the working environment. Keywords : Working Environment, Practice of Â Pesticide Management, Worker, Pesticide Poisoning.